Laparoscopic hemicolectomy in a patient with situs inversus totalis after open distal gastrectomy - Sumi, Yasuo (Baishideng Publishing Group Co., Limited, 2013)
Situs inversus totalis (SIT) is a rare anomaly in which the abdominal and thoracic cavity structures are opposite their usual positions. Occasionally, a few patients with a combination of this condition and malignant tumors have been encountered. Recently, several laparoscopic operations have been reported in patients with SIT. We report a case of an 83-year-old man with situs inversus totalis who developed colon cancer after open distal gastrectomy. Laparoscopic hemicolectomy with radical lymphadenectomy in such a patient was successfully performed by careful consideration of the mirror-image anatomy. Techniques themselves was not different from those in ordinary cases. Thus, curative laparoscopic surgery for colon cancer in the presence of situs inversus totalis is feasible and safe.